Caspase 3 activation and PARP cleavage in lymphocytes from newborn babies of diabetic mothers with unbalanced glycaemic control. (25th April 2013) - Tarquini, F.; Tiribuzi, R.; Crispoltoni, L.; Porcellati, S.; Del Pino, A. M.; Orlacchio, A.; Coata, G.; Arnone, S.; Torlone, E.; Cappuccini, B.; Di Renzo, G. C.; Orlacchio, A.
<x xml:space="preserve">Abstract</x> Several epidemiological studies showed that gestational diabetes mellitus is the most frequent metabolic disorder of pregnancy, the pathogenesis of which has yet to be completely clarified. The aim of this study was to investigate the presence and processing of caspase 3 (Casp3) and poly(ADP‐ribose) polymerase 1 (PARP1) in cord blood lymphocytes as markers of apoptosis in relation to glycaemic control during intrauterine life. Our results showed a specific positive correlation between the levels of active Casp3 (17–19 kDa) and the inactive form of PARP1 (89 kDa) in lymphocytes isolated from newborn babies of diabetic women with unbalanced glycaemic control, with a direct correlation between the activation of casp3 and the inactivation of PARP1, that makes lymphocytes unresponsive towards lipopolysaccharide stimulation, highlighting an altered functional response. Besides more studies are required to fully correlate the activation of the apoptotic process during the intrauterine life with the foetal health later in life, our study indicates that a cord blood lymphocyte, an easily accessible source, is informative about the activation of apoptotic stimuli in circulating cells of newborn babies in relation to the glycaemic control reached by the mother during pregnancy. Copyright © 2013 John Wiley & Sons, Ltd.